Atmospheric Ionizations by Solar X‐Rays, Solar Protons, and Radiation Belt Electrons in September 2017 Space Weather Event - Kiyoka Murase; Ryuho Kataoka; Takanori Nishiyama; Kaoru Sato; Masaki Tsutsumi; Yoshimasa Tanaka; Yasunobu Ogawa; Tatsuhiko Sato (Space Weather)
Abstract Energetic particles from space deposit their energies on the Earth's atmosphere and contribute to variations in the concentration of neutral components such as ozone which controls the atmospheric temperature balance. Comprehensive understandings of their global impact on the atmosphere require whole pictures of spatiotemporal ionization distributions due to them. We first attempt to evaluate and summarize the altitude profiles of ionization for the September 2017 space weather event with cutting‐edge space‐borne and ground‐based observations of different types of particle inputs. In early September 2017, the Sun showed notable activity, including X‐class flares and solar proton events. During this period, ground‐based radar observations have confirmed atmospheric ionization events by energetic particle precipitations of solar flare X‐rays, solar protons, and radiation belt electrons, the main sources of ionization into the Earth's atmosphere. We estimate the altitude profiles of the ionization rate by using the Particle and Heavy Ion Transport code System (PHITS) with the input of the particle fluxes obtained by satellites. The estimates are then compared with measurements of the ionization altitude, ionization intensity, and electron density by the radars in the polar region, such as the PANSY radar at Syowa Station and the EISCAT in Tromsø, Norway. We conclude that the PHITS simulation results reasonably reproduce (within the error of a factor of two) those ionizations measured by ground‐based instruments with inputs of observed ionization sources by satellites.